“Do the editors-in-chief of Iranian medical journals have a good Knowledge, attitude and practice of plagiarism?” - Abbasiyan, Zohreh; Shekofteh, Maryam; Afshar, Ebrahim; Ghasemi, Erfan; Rahimi, Forough (Archives of Advances in Biosciences, 2018)
Plagiarism is one of the misconducts which are specifically observed in scientific journals. It is important to prevent and reduce it in scientific communities. The chief editors of journals can play an effective role in this regard. Therefore, this study aims to determine the knowledge, attitude, and the practice (KAP) of the chief editors of scholarly journals in Universities of Iran about plagiarism. The data for this descriptive survey were collected through a researcher-made questionnaire which was developed and validated in three sections of knowledge, attitude, and practice. The statistical population of the study included all the chief editors of scholarly journals in Universities of Medical Sciences in Tehran. The scores of the editors were calculated separately in each section. The data collection procedure was followed either by email or in-person. The collected data were analyzed through SPSS. The chief editors’ score is %88.8 in the section of “knowledge of plagiarism” which represents a high score. The chief editors’ “attitude toward plagiarism” indicates a high level (%61.3), which represents a negative attitude of plagiarism, and their “practice” is also at a mid-level approaching towards high level. In general, the knowledge, attitude, and practice of chief editors about plagiarism are in a better status comparing to similar studies. However, it is expected that the editors in chief achieve a more favorable level in this regard.